Justice above all selected judgments of Tun Arifin bin Zakaria with commentaries - Arifin Zakaria 1950- (Sweet & Maxwell/Thomson Reuter, 2017)
Justice Above All contains a selection of the judgments of Malaysia's thirteenth Chief Justice, Tun Arifin bin Zakaria, carefully chosen from the many judgments delivered by the distinguished jurist over a wide range of subjects. These judgments are juxtaposed against analytical commentaries prepared by 32 eminent contributors from the legal fraternity, amongst whom include two former Chief Justices of Malaysia and the current Chief Justice of Singapore. The commentaries include references to related cases, discussion on the legal background relevant to the judgment and the development of the law after the judgment, as well as a review of the application of the judgment in subsequent court decisions. This unique publication is published in recognition of the vast contributions of Tun Arifin not only to the scholarship of law, but also to the business of the administration of justice. It will no doubt take its rightful place in the history of the development of Malaysian law and should be available for reference in all law firms and libraries.